ChemInform Abstract: Aerobic Oxygenative Cleavage of Electron Deficient C—C Triple Bonds in the Gold‐Catalyzed Cyclization of 1, 6‐Enynes. Issue 12 (March 2015) - Patil, Dilip V.; Park, Hyun‐Sub; Koo, Jaeyoung; Han, Jin Wook; Shin, Seunghoon
Abstract 19 examples